Comparing Administrative Data and Resident Assessment Instrument Data for Mental Health Surveillance in Home Care and Long‐Term Care Populations - Ruth Ann Marrie; James M. Bolton; Xueyi Chen; Erind Dvorani; Okechukwu Ekuma; Zahra Goodarzi; Andrea Gruneir; Jin Luo; Nathan Herrmann; Matthias Hoben; David B. Hogan; Andrea Iaboni; et al. (International Journal of Methods in Psychiatric Research, 2026)
ABSTRACT Objectives To compare mental illness prevalence, and agreement between mental illness measures, in home care (HC) and long‐term care (LTC) using administrative definitions and Resident Assessment Instrument (RAI)‐diagnoses. Methods Applying a common protocol to linked administrative‐RAI datasets in Alberta, Manitoba, and Ontario, Canada, we selected adults receiving HC or LTC between 2012 and 2023. Cross‐sectionally, we compared administrative definitions with RAI‐diagnoses (depression, anxiety, bipolar disorder and schizophrenia) using kappa, sensitivity, specificity, positive and negative predictive value. We examined discordance‐associated factors using multivariable logistic regression. Results Depression was the most prevalent mental illness (administrative data, HC: 29%–34% of 493,895 people; LTC: 21%–51% of 357,117 people). Prevalence estimates were consistently lower using RAI‐diagnoses than administrative definitions. Agreement between data sources was moderate for depression ( k = 0.33–0.57) and anxiety disorders ( k = 0.35–0.63). Younger age, dementia, and more physician visits were associated with higher likelihood of discordance between data sources; male sex had a lower likelihood. Conclusion While mental illness prevalence is high in HC and LTC populations, RAI‐based estimates are lower than administrative data estimates. Discordance between data sources differs by individual characteristics. Concurrent comparison of RAI‐diagnoses and administrative data to a gold standard clinical interview would clarify the optimal surveillance strategy.